Hubungan Antara Aktivitas Poligalakturonase dengan Virulensi RAS 4 Fusarium oxysporum f.sp. cubense - Arif Wibowo; Siti Subandiyah; Christanti Sumardiyono; Liliek Sulistyowati; Peter Taylor (Jurnal Perlindungan Tanaman Indonesia, 2008)
One of the major constraints of banana plantation in Indonesia is the occurrence of fusarium wilt disease caused by Fusarium oxysporum f.sp. cubense. The pathogen produced series of cell wall degradation extracellular enzymes which have important roles in pathogenicity. Many studies have been conducted to know the role of degrading enzyme banana pectin is the major component of cell wall. Many pectinolytic enzymes such as polygalacturonase and others have been isolated from many fungal plant pathogens. The study was aimed to know the role of polygalacturonase towards the virulence of race 4 of F. oxysporum f.sp. cubense. The result showed that from 10 isolates of race 4 of F. oxysporum f.sp. cubense, the most virulent isolate was Lmp1 followed by Srg1, Bgl6, Mln1, Bgl3, A13, Bnt2, Gnk3, Kjg1 dan Wsb5. This was indicated by high and low percentage of wilting leaves of banana cultivar Cavendish when they were inoculated with these isolates. Incubation period varied from 3 to 6 weeks after inoculation SDS-PAGE showed that polygalacturonase, mostly PG1 and PG2, was secreted by these isolates, whereas PG3 was only found in growing cultures of Gnk3 and Wsb5 isolates. Detection of polygalacturonase activity with diffusion agar and reducing sugar methods showed that the activity of polygalacturonase secreted by F. oxysporum f.sp. cubense in the growing culture had no correlation with the virulence of the fungal pathogen.